The changing nature of human-forced hydroclimatic risks across Africa - Schlosser, C. Adam; Sokolov, Andrei; Gao, Xiang; Thomas, Timothy S.; Strzepek, Ken (Massachusetts Institute of Technology, 2023)
We present results from large ensembles of projected 21st century changes in seasonal precipitation and near-surface air temperature over Africa and selected sub-continental regions. These ensembles are a result of combining Monte Carlo projections from a human-Earth system model of intermediate complexity with pattern-scaled responses from climate models of the Coupled Model Intercomparison Project Phase 6. These future ensemble scenarios consider a range of global actions to abate emissions through the 21st century. We evaluate distributions of surface-air temperature and precipitation change. In all regions, we find that without any emissions or climate targets in place, there is a greater than 50% likelihood that mid-century temperatures will increase threefold over the current climate’s two-standard deviation range of variability. However, scenarios that consider more aggressive climate targets all but eliminate the risk of these salient temperature increases. A preponderance of risk toward decreased precipitation exists for much of the southern Africa region considered, and this is also compounded by enhanced warming (relative to the global trajectory). Over eastern and western Africa, the preponderance of risk in increased precipitation change is seen. Strong climate targets abate evolving regional hydroclimatic risks. Under a target to limit global climate warming to 1.5˚C by 2100, the risk of precipitation changes within Africa toward the end of this century (2065-2074) is commensurate to the risk during the 2030s without any global climate target. Thus, these regional hydroclimate risks over much Africa could be delayed by 30 years, and in doing so, provide invaluable lead-time for national efforts to prepare, fortify, and/or adapt.